2006
DOI: 10.1111/j.1471-1842.2006.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge in the Palm of your hands: PDAs in the clinical setting

Abstract: Objective: To explore the impact of hand-held computers on patient care by identifying: (i) how often clinical staff accessed resources on hand-held computers to inform their clinical decision making; (ii) Which hand-held resources were thought to be most useful in the clinical setting; (iii) the barriers to using hand-held resources to support patient care. Design: A descriptive study comparing aspects of Personal Digital Assistant (PDA) resource use in two phases, between August 2002 and December 2003. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 7 publications
0
41
0
2
Order By: Relevance
“…These devices, also known as handhelds, allow health professionals to find answers to clinical questions while at the patient's bedside, resulting in better patient safety and clinical outcomes [3]. However, it has been found that PDA users, especially medical students, often struggle to use these tools to their full potential [4][5][6][7].…”
mentioning
confidence: 99%
“…These devices, also known as handhelds, allow health professionals to find answers to clinical questions while at the patient's bedside, resulting in better patient safety and clinical outcomes [3]. However, it has been found that PDA users, especially medical students, often struggle to use these tools to their full potential [4][5][6][7].…”
mentioning
confidence: 99%
“…All students were beginners at elearning on mobile devices. According to previous studies 4,[6][7][8][9][10] , it has been reported that there are barriers to elearning on mobile devices for beginners: e.g. lack of time to learn how to use the resource, difficulties installing software applications and lack of knowledge about handling mobile devices.…”
Section: Discussionmentioning
confidence: 99%
“…They have improved battery life, sufficient capacity to store information, and wireless web access 3,4) . Compared with traditional personal computers, the characteristics of mobile devices allow users to access information conveniently and without the constraints of time and place 6) . In this paper, we consider how mobile devices can enhance opportunities for self-learning, especially from the standpoint of convenient access to information.…”
Section: Introductionmentioning
confidence: 99%
“…In some settings librarians, sometimes called informationists in this context, are becoming part of the clinical team, available to provide information on the ward (Davidoff and Florance 2000;Rankin, Canto, and Grefsheim 2008). In other cases, library services provide information directly to clinicians via mobile devices like Personal Digital Assistants (PDAs) (Honeybourne, Sutton, and Ward 2006;Burnette and Dorsch 2006). Increasingly, they respond directly not only to professionals but also to the needs of patients and the general public (Stahl 2001).…”
Section: Developing the Rolementioning
confidence: 98%